2021
DOI: 10.32890/ijbf2021.16.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy Prediction: Smes in the Hospitality Industry

Abstract: The objectives of this study are to predict bankruptcy risk among SMEs in the hospitality industry for a three-year horizon period and to investigate the factors that are significant in determining bankruptcy. The contribution of SMEs in the hospitality industry is essential as businesses in the hospitality industry are dominated by SME operators. However, the failure rate among SMEs is relatively high and almost 50 percent of hospitality establishments do not survive beyond five years of operation. The Stepwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…= 0.000). This is consistent with Abidin et al (2021), who showed that the probability of failure decreases with age. Belda & Cabrer-Borrás (2021) also show that the survival rate increases with age.…”
Section: Robustness Testssupporting
confidence: 92%
See 4 more Smart Citations
“…= 0.000). This is consistent with Abidin et al (2021), who showed that the probability of failure decreases with age. Belda & Cabrer-Borrás (2021) also show that the survival rate increases with age.…”
Section: Robustness Testssupporting
confidence: 92%
“…Over-indebtedness (ONEG) impacts the probability of financial distress for both sub-branches. This confirms the general view that an increase in debt leads to an increase in risk for tourism firms (Abidin et al, 2021;Axioglou & Christoulakis, 2021;Upneja & Dalbor, 2001).…”
Section: Robustness Testssupporting
confidence: 83%
See 3 more Smart Citations